The Effect of Clarity of Budget Targets and Decentralization on Regional Government Performance (Empirical Study at the Department of Industry and Trade, North Sulawesi Province) - Wehara Mariana Sigar; David P. E. Saerang; Sonny Pangerapan (Formosa Journal of Applied Sciences, 2023)
The aim of this research is to find out whether clarity of budget targets and decentralization have a partial and simultaneous effect on local government performance. This hypothesis was tested using the t test and f test. The research sample consisted of 31 employees, namely ASN in the Secretariat sector, Legal and Personnel Sub-Section, and Planning and Finance Sub-Section, and the Head of the Department of Industry and Trade. The research method uses a questionnaire with Likert scale measurements. The analytical method used is multiple linear regression analysis where the data analysis process is carried out using SPSS version 26 computer technology. The results of this research show that clarity of budget targets has a positive and significant effect on local government performance, while partial decentralization has no effect on performance. local government; Furthermore, clarity of budget targets and decentralization simultaneously influence regional government performance.